The Relationship between Family’s Assessment Support and MDR TB Patient’s Adherence on Treatment in RSUD Dr. Soetomo Surabaya - Safira Nur Ainiyah; Soedarsono Soedarsono; Pirlina Umiastuti (Juxta: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2019)
Introduction: Multi Drug-Resistant Tuberculosis (MDR TB) is caused by Mycobacterium tuberculosis and has been resistant to isoniazid and rifampicin. Its treatment needs long time and causes some side effects which can make the patients non-adherent so that family support is needed. This study aims to know the relationship between family’s assessment support and MDR TB patient’s adherence on treatment in RSUD Dr. Soetomo Surabaya.